The risk of injuries during work and its association with precipitation: New insight from a sentinel-based surveillance and a case-crossover design - Tian, Tian; Lin, Xiao; Huang, Tingyuan; Zhang, Kai; Shi, Congxing; Wang, Pengyu; Chen, Shimin; Guo, Tong; Li, Zhiqiang; Qin, Pengzhe; Liang, Boheng; Zhang, Wangjian; et al. (Frontiers in Public Health, 2023)
Background: Injuries during work are often exogenous and can be easily influenced by environmental factors, especially weather conditions. Precipitation, a crucial weather factor, has been linked to unintentional injuries, yet evidence of its effect on work-related injuries is limited. Therefore, we aimed to clarify the impact of precipitation on injuries during work as well as its variation across numerous vulnerability features. Methods: Records on the work-related injury during 2016-2020 were obtained from four sentinel hospitals in Guangzhou, China, and were matched with the daily weather data during the same period. We applied a time-stratified case-crossover design followed by a conditional logistic regression to evaluate the association between precipitation and work-related injuries. Covariates included wind speed, sunlight, temperature, SO2, NO2 and PM2.5. Results were also stratified by multiple factors to identify the most vulnerable subgroups. Results: Daily precipitation was a positive predictor of work-related injuries, with each 10 mm increase in precipitation being associated with an increase of 1.57% in the rate of injuries on the same day and 1.47%-1.14% increase of injuries on subsequent three days. The results revealed that precipitation had a higher effect on work-related injuries in winter (4.92%; 95%CI: 1.77-8.17%). The elderly (2.07%; 95%CI: 0.64-3.51%), male (1.81%; 95%CI: 0.96-2.66%) workers or those with lower educational levels (2.58%; 95%CI: 1.59-3.54%) were more likely to suffer from injuries on rainy days. There was a higher risk for work-related injuries caused by falls (2.63%; 95%CI: 0.78-4.52%) or the use of glass products (1.75%; 95%CI: 0.49-3.02%) on rainy days. Conclusions: Precipitation was a prominent risk factor for work-related injury, and its adverse effect might endure for three days. Certain sub-groups of workers were more vulnerable to injuries in the rain.